2013
DOI: 10.1002/ange.201305711
|View full text |Cite
|
Sign up to set email alerts
|

[2+2+2] Cycloadditions of Siloxy Alkynes with 1,2‐Diazines: From Reaction Discovery to Identification of an Antiglycolytic Chemotype

Abstract: The synthesis of new nitrogen-containing heterocycles plays a pivotal role in chemical biology and medicinal chemistry, as reflected by their many applications in the development of pharmacological probes and drugs. [1] Despite notable progress, there is a significant need for the identification of new nitrogen heterocycles which target previously unexplored regions of biogenic chemical space. Among the many possible synthetic strategies to such compounds, cycloadditions involving C-N multiple bonds are partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For example, Rawal, Kozmin, and co-workers demonstrated that pyridinium triflimide could serve as an efficient catalyst in an interesting cycloaddition reaction of siloxy alkynes with 1,2-diazines, leading to a range of bioactive polyheterocyclic compounds. 204 In addition to forming adducts with amines as useful Brønsted acid catalysts, triflimide has been extremely successful in forming adducts with Lewis acids to achieve Brønsted acid-assisted Lewis acids. A notable example is the adducts between triflimide and chiral oxazaborolidines first introduced by Ryu and Corey in 2003 (Scheme 103).…”
Section: Use As a Cocatalyst Or Additivementioning
confidence: 99%
“…For example, Rawal, Kozmin, and co-workers demonstrated that pyridinium triflimide could serve as an efficient catalyst in an interesting cycloaddition reaction of siloxy alkynes with 1,2-diazines, leading to a range of bioactive polyheterocyclic compounds. 204 In addition to forming adducts with amines as useful Brønsted acid catalysts, triflimide has been extremely successful in forming adducts with Lewis acids to achieve Brønsted acid-assisted Lewis acids. A notable example is the adducts between triflimide and chiral oxazaborolidines first introduced by Ryu and Corey in 2003 (Scheme 103).…”
Section: Use As a Cocatalyst Or Additivementioning
confidence: 99%
“…This class of compounds also possesses an N‐heterocyclic ring, which makes them suitable as ligands for coordination to a SABRE catalyst 3,27,38 (Figure 2B). We synthesised 39,40 and tested the four TP isomers, alongside studies involving the inclusion of a fully deuterated isotopologue as co‐ligand to increase percentage polarization. To extend magnetization lifetimes and enhance the timing window for subsequent imaging we also explored application of pseudo‐long lived state strategies 41,42 .…”
Section: Introductionmentioning
confidence: 99%
“…(A) Structure of the thienopyridazines synthesised 39,40 and hyperpolarized in this study by SABRE, Thieno[2,3‐ d ]pyridazine, (T[2,3‐ d ]P), Thieno[3,4‐ d ]pyridazine (T[3,4‐ d ]P), Thieno[2,3‐ c ]pyridazine (T[2,3‐ c ]P), Thieno[3,2‐ c ]pyridazine (T[3,2‐ c ]P). (B) Potential active SABRE catalyst [IrH 2 (IMes)(T[2,3‐ d ]P) 3 ]Cl; n is T[2,3‐ d ]P and omitted for clarity…”
Section: Introductionmentioning
confidence: 99%